Differences in Parental Knowledge About ISPA Prevention In Toddlers Before and After Being Given PocketBooks - Ika Wijayanti; Fachry Amal; Haerani Haerani (Journal of Midwifery Science: Basic and Applied Research, 2021)
ISPA in toddlers is very dangerous if not treated immediately, so there needs to be health education with a pocket book on how to prevent ISPA in toddlers. Pocket Book Media is a tool in the form of a book, equipped with writing and pictures that can cover many people, practical in its use because it can be used anywhere. The purpose of this study was whether there was a difference in the knowledge of parents about the prevention of ISPA in toddlers before and after being given a pocket book in the work area of the Hebeybhlu Yoka Health Center. This research method uses a quasi-experimental approach with aapproach  one group pretest – posttest design. The population in this study were Toddlers who suffered from ISPA in January-February 2021 in the Hebeybhulu Yoka Health Center area totaling 56 people, while the sample using random sampling technique was 15 people. The data collection instrument used a questionnaire. The results showed that there was a difference before and after being given a Pocket Book with p volume 0.000 p volume (0.05).Keyword : Buku Saku, ISPA Pada Balita, Pencegahan ISPA.